Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.cegh.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction towards the services provided by the community pharmacist in north-west India: A qualitative exploratory study

Abstract: Introduction: Patient satisfaction is an indicator in identifying and assessing the patient health-related needs, it is an important factor in determining the health care facilitates being delivered to the patients. The Community Pharmacist-led quality of services can be accessed through patient-reported outcomes (PROs). A cross-sectional survey was conducted to assess the level of client/patient satisfaction towards the services provided by the Community Pharmacist and factors affecting it. Methods: A descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The majority perceived the pharmacist as a medication expert, health counselor, health promoter, and patient-centered practitioner, reflected by the enhanced satisfaction scores among those who reported receiving advice on lifestyle habits from their pharmacist. These results underscore the importance of pharmacists educating their clients about nonpharmacological options for treatment (Kang et al, 2017) and align with previous findings showing decreased patient satisfaction with pharmacists who did not offer guidance on non-pharmacological approaches to managing diseases (Chhabra et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…The majority perceived the pharmacist as a medication expert, health counselor, health promoter, and patient-centered practitioner, reflected by the enhanced satisfaction scores among those who reported receiving advice on lifestyle habits from their pharmacist. These results underscore the importance of pharmacists educating their clients about nonpharmacological options for treatment (Kang et al, 2017) and align with previous findings showing decreased patient satisfaction with pharmacists who did not offer guidance on non-pharmacological approaches to managing diseases (Chhabra et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…However, there was disagreement with a study conducted in India showing that unemployed patients were less satisfied in community pharmacy services. 18 Generally, illiterate patients were associated with lowest satisfaction ranks in consultation and service delivery qualities as you can see in their mean ranks 164.52 and 159.37 respectively (Table 3). They were highly frustrated in pharmacist's advices about proper medication use than those of secondary (adjusted p-value=0.041) and those of primary (adjusted p-value=0.023) (Table 4).…”
Section: Discussionmentioning
confidence: 87%
“…There is a consistency with a 2019 study established in North-West India showing that higher number of patients (39.5%) were dissatisfied in pharmacist's counselling. 18 It was found that the lowest level of satisfaction in consultation is associated with 'explaining on the possible side effects, and telling the precautions (e.g. activities to avoid.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanied with day to day activities the community pharmacies in India have made them prove as significant contributors to public health. As observed by Chhabra et al (2019), community pharmacies are considered as the independent craftsperson to the public health service by dispensing medicines and giving advice. It also can be analyzed by the findings that a number of key policies have outlined the areas pharmacists that should be advanced further in order to serve better public health services.…”
Section: Data Analysis 41 the Role Of Community Pharmacy In Managing ...mentioning
confidence: 99%